Systematic investigation on the effect of crosslinking agent type and dosage on the performance of TPU/MVQ based thermoplastic vulcanizates - Cui, Zi Wen; Jing, Yuan Rong; Liu, Su Su; Liu, Guang Yong (Journal of applied polymer science, 2021)
Dynamic vulcanized thermoplastic polyurethane (TPU)/methyl vinyl silicone rubber (MVQ) thermoplastic vulcanizates (TPVs) were prepared in torque rheometer. The influence of the type and amount of peroxide crosslinking agent on the mechanical properties, thermal stability, micromorphology and melt flowability was systematically investigated. The results showed that the mechanical properties of the TPVs vulcanized by 2,5‐dimethyl‐2,5‐di (tert‐butyl peroxy) hexane (DBPH) first increased and then decreased with increasing the peroxide amount, while for dicumyl peroxide (DCP) vulcanizing system the mechanical properties slowly increased. Besides, the comprehensive mechanical properties vulcanized by DBPH were better than those of DCP group. The results of the thermogravimetric analysis showed that the TPVs vulcanized by DBPH had better heat stability, corresponding to the excellent thermo‐oxidative aging performance and the 38% increase in tensile strength after aging. In addition, the MVQ rubber particles showed better dispersing performance for DBPH vulcanizing system. The melt flow rate of the TPVs showed a linear relationship with increasing DBPH dosage and became worse after the amount of crosslinking agent exceeded 1.5 phr. By comprehensive comparison, the TPVs have better performance when use peroxide DBPH as the crosslinking agent and the dosage is 1.5 phr.